Paraneoplastic leukemoid reactions induced by cytokine-secreting tumours. Issue 6 (15th January 2020) - Abukhiran, Ibrahim A; Jasser, Judy; Syrbu, Sergei
Abstract : Paraneoplastic leukemoid reaction (PLR) is the extreme leukocytosis that occurs due to a non-haematolymphoid cytokine-secreting tumour (CST) in the absence of bone marrow infiltration by that solid tumour. The clinical presentation is widely variable, and therefore challenging. If the underlying malignancy is not clinically apparent, PLR could be mistaken for myeloproliferative neoplasms, altering the patient's management. CSTs are highly aggressive tumours associated with a poor prognosis due to multiple mechanisms. Localising and treating the underlying malignancy is the mainstay of treatment. Both the treating clinician and the pathologist should keep a high level of suspicion for this entity in patients having unexplained leukocytosis. We herein discuss the underlying mechanisms, clinical presentation, pathological features, differential diagnosis and prognosis of this rare entity. An emphasis on the role of the pathologist is provided since the lack of knowledge on this entity can lead to dramatic effects on the patient, including unnecessary diagnostic testing and treatments.